The rebound effect in the treatment of complex hemangioma with interferon alpha 2A - Jaime Anger; Carneiro, Ricardo Gama; Pinus, José; Ernesto, José Manoel; Faiwichow, Guido (São Paulo Medical Journal, 1998)
The authors report the case of an infant with an extensive face hemangioma with subglottic airway obstruction which had been successfully treated with interferon alpha 2A but then reoccurred with the same dimensions and airway blockage after treatment was abruptly interrupted. The authors suggest the implementation of a standard procedure for the interruption of interferon alpha 2A treatment in order to avoid this rebound effect and advise on the need for further studies to properly evaluate dosage and administration parameters for interferon alpha 2A in the treatment of difficult hemangioma.